44th AIAA Aerospace Sciences Meeting and Exhibit 2006
DOI: 10.2514/6.2006-1517
|View full text |Cite
|
Sign up to set email alerts
|

Breakup of Turbulent and Non-Turbulent Liquid jets in Gaseous Crossflows

Abstract: An experimental and computational investigation of the primary breakup of nonturbulent and turbulent round liquid jets in gas crossflow is described. Pulsed shadowgraph and holograph observations of jet primary breakup regimes, conditions for the onset of breakup, properties of waves observed along the liquid surface, drop size and velocity properties resulting from breakup and conditions required for the breakup of the liquid column as a whole, were obtained for air crossflows at normal temperature and pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
19
2
Order By: Relevance
“…Presumably these larger structures accelerate process of jet disintegration by aerodynamic shearing. It is worth to note that distances at which fuel jet disintegrates in this study are much shorter compared to prior studies (Wu et al, 1997;Sallam et al, 2004) that reported the CBP to lie at a distance of 8 diameters downstream of the orifice for most of the investigated cases. This discrepancy can be attributed to the difference of operating conditions and measuring techniques used for the CBP locating.…”
Section: Fig 14 Experimental Schematic For the Liquid Jet Light Guimentioning
confidence: 62%
See 1 more Smart Citation
“…Presumably these larger structures accelerate process of jet disintegration by aerodynamic shearing. It is worth to note that distances at which fuel jet disintegrates in this study are much shorter compared to prior studies (Wu et al, 1997;Sallam et al, 2004) that reported the CBP to lie at a distance of 8 diameters downstream of the orifice for most of the investigated cases. This discrepancy can be attributed to the difference of operating conditions and measuring techniques used for the CBP locating.…”
Section: Fig 14 Experimental Schematic For the Liquid Jet Light Guimentioning
confidence: 62%
“…Other researchers (Sallam et al, 2004) measured column breakup point at We range of 0.5-260. Their studies yielded different value of t b /t* = 2.5.…”
Section: Introductionmentioning
confidence: 99%
“…Both sub-and supersonic cross-flows were examined, and the breakup mechanism of the single liquid jet was experimentally investigated. Instant shadowgraph pictures showed that the liquid column breakup resembles the secondary breakup of a spherical droplet flying in a stagnant gas [3]. The somewhat quantitative nature of the jet column fracture was also addressed in view of the wave parameters.…”
Section: Introductionmentioning
confidence: 98%
“…In-depth macroscopic studies on the spray formation in a cross flow have been made and generally focused on elucidating the spray appearance, penetration heights, velocity fields, and effects of liquid property [1][2][3][4][5]. Both sub-and supersonic cross-flows were examined, and the breakup mechanism of the single liquid jet was experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation